Mood States on Working Memory and Brain Haemodynamic Response Using Optical Topography Modality - FENG, YING XING (2017)
Higher cognitive brain functions such as language, planning and problem solving require the working memory (WM). Studies have shown that negative mood states impair the WM functions, related to activations at the prefrontal cortex (PFC) region. Previous works which were conducted based on Japanese and German subjects have reported a significant correlation between negative mood states and reduced PFC activation during the verbal WM task, however no significant correlation was found during the visuospatial WM task.